Does corruption hinder investment? Evidence from Russian regions - Nikita Zakharov (University of Freiburg, Department of International Economic Policy (iep), 2017)
This paper investigates the causal relationship between corruption and fixed capital investment in Russian regions. The panel data on corruption allow to control for unobserved heterogeneity with fixed effects estimation. We address the problem of endogeneity by introducing novel instrumental variables for corruption: the presence of free press and violations of journalists' rights. Our main result is the strong negative effect of corruption on aggregate investment in fixed capital. Disaggregating investment by ownership, we find that corruption decreases private investment, but not investment made by state-owned companies. The effect is larger for companies with foreign ownership. We also observe a strong negative relationship between regional import of capital goods and corruption.
Keywords: E22; K42; L26; P26; 330; Corruption; Investment; Russia; Freedom of Press; Import of Capital Goods